Perencanaan Desain Bak Kontrol Dalam Upaya Pengendalian Sedimentasi Pada Saluran Drainase Kelurahan Damai Baru Kota Balikpapan - Pongtuluran, Ezra Hartarto; Fatmawati, Fatmawati; Rio, Wahyu Yusuf (Jurnal Teknologi Terpadu, 2025)
The area of Kalimaya road, Balikpapan City is an area that still experiences flood problems. One of the main factors is the lack of optimal performance of the existing drainage channels due to the high sedimentation from the upstream area, precisely from the vacant land that is planned to be built housing but has not been carried out so that when heavy rain indirectly brings sediment from the area to spread along the drainage channel.Control basin is planned to minimize the load of sediment volume that occurs along the channel, The form of analysis that will be carried out is by making a location mapping and land use, then determining the amount of erosion rate from the source of the sediment location. The size of the erosion rate is used as a reference in determining the volume of sediment that will enter the drainage channel.The results show that the erosion from the area around the drainage channel with the source of the vacant land use is 88.101 tons/km2/year. From the results of the erosion rate, it can be determined that the sediment rate is 15,700 tons/km2/year with a total sediment volume in one year is 5,965m3. With the volume of sediment in the channel, the form of control tank planning design required to accommodate sediment that occurs in the drainage channel with a service plan life of one year is 4.00 meters long, 1.20 meters wide, and 1.24 meters deep.